2012
DOI: 10.1111/nin.12014
|View full text |Cite
|
Sign up to set email alerts
|

Include, differentiate and manage: gay male youth, stigma and healthcare utilization

Abstract: In Canada, there has been a recent increase in HIV incidence among young men who have sex with men. However, gay male youth (GMY) may forego HIV testing due to fear of stigmatization. Therefore, the aim of this research was to explore the perceptions of stigma in health care within this population. The research was conducted through a series of semi-structured interviews with eight GMY aged 20-29, who frequented a gay-friendly clinic in downtown Ottawa, Canada. In a sub-analysis of the interviews utilizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…For objective 1, the usage numbers indicated an increase in both the uptake and proportion of patients undergoing repeat testing, which suggests, as previous research with men from GayZone identified, 24 that this clinic is well liked by MSM. Further supporting that GayZone is well used are the public health laboratory figures from 2011 (most recent available), 26 GayZone patients have GPs, led us to believe that some MSM may simply prefer accessing STI/HIV testing at GayZone, thus satisfying objective 1.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…For objective 1, the usage numbers indicated an increase in both the uptake and proportion of patients undergoing repeat testing, which suggests, as previous research with men from GayZone identified, 24 that this clinic is well liked by MSM. Further supporting that GayZone is well used are the public health laboratory figures from 2011 (most recent available), 26 GayZone patients have GPs, led us to believe that some MSM may simply prefer accessing STI/HIV testing at GayZone, thus satisfying objective 1.…”
Section: Discussionsupporting
confidence: 51%
“…Rationales included: same-day access through walk-in services; perceived comprehensiveness of testing and specialized knowledge; desires not to discuss sexual practices with general practitioners (GPs); availability of anonymous or point-of-care testing; and referral, e.g., for a second opinion or specialized treatment. [22][23][24] In one study, obtaining testing for all STIs/HIV (comprehensiveness) and perceived specialized knowledge at STI clinics resulted in some persons who first sought care with their GPs subsequently visiting STI/HIV clinics to obtain the testing they felt their GPs missed. 25 In this study, STI/HIV testing with GPs resulted in duplicate service utilization.…”
Section: Reasons For Accessing An Sti/hiv Clinicmentioning
confidence: 99%
“…Worldwide, youth are often viewed as immature individuals who are not ‘ready’ to make the ‘right’ decisions regarding their sexual lives, and parents are expected to monitor and inform their decision about sexual and reproductive health [ 31 ]. However, in the context of Iran and several other conservative settings, parents often try to stick to the socio-cultural norms around sexuality (e.g., abstinence, delaying first sexual experience) and discussions around such topics remain very limited if they ever take place [ 31 , 32 ]. Moreover, many parents are often not equipped with sufficient knowledge to provide their children with sexual health education in the context of HIV [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tied to heteronormativity are homophobic reactions from health care providers. For example, O'Byrne and Watts (), in their study in Canada, found that gay male youths interpreted the attitudes of health professionals as judgemental. Being gay was associated with having a high risk of contracting HIV/STIs.…”
Section: Resultsmentioning
confidence: 99%